Hierarchically porous piezoresistive sensor for application to the cambered palm of climbing robot with a high payload capacity. (26th May 2021) - Wang, Ziya; Zhu, Zhihao; Huang, Huayi; Zhao, Wenyu; Xu, Yingtian; Zheng, Zhenliang; Ding, Ning
Abstract: Effective sensitivity within a large responding range is a crucial parameter of flexible tactile sensors for a robot, especially for engineering climbing robots under high shear force conditions. While introducing microstructures can improve the sensitivity, in turn, it leads to a limited pressure-response range due to the poor structural compressibility. To achieve effective sensing under large loading forces, the flexible sensor needs to have a hierarchical sensing system and an optimal mechanic design. Herein, we report a strategy of embedded hierarchically porous piezoresistive foam that can significantly boost the sensitivity ( S min > 0.084 kPa −1 at 20 Pa–500 kPa) while simultaneously broadening the pressure responding range, together with remarkable mechanical stability and robustness. Depending on the pressure distribution of the appreciable palm, the climbing robot with a high payload (40 kg) was demonstrated a series of recognitions of obstacles and feedback controls at slipping state. The soft piezoresistive material with the assembly architecture would be a general design expected to be applied to other types of robots to achieve a broader pressure-response range and a higher sensitivity.